2020
DOI: 10.1177/2374373520975728
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Patient Engagement in an HIV Clinical Research Program: A Qualitative Analysis of Stakeholder Accounts

Abstract: Patient engagement (PE) promotes collaboration between stakeholders (researchers, patients, clinicians, etc). It often faces challenges due to tensions between its ethical/political and scientific underpinnings. This article explores how stakeholders applied the guiding principles of a PE project (“co-build,” “support and mutual respect,” and “inclusiveness”) for an HIV clinical research program initiated in January 2016. Three researchers/clinicians, a PE agent, and 2 patients held 3 meetings (June-October 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…[46][47][48][49] Attention to structural level drivers of health inequity is a key element of patient-centered-care 50,51 and a critical component of meaningful community engagement. 52,53 Anecdotal evidence suggests that study personnel are sometimes reluctant to enroll women whom they perceive as potentially unable to complete the study and likely to leave the study prematurely which would reflect poorly on the enrolling clinical site. A 2007 survey of ACTG study coordinators and nurses found that women, people color, and people with a history of injection drug use were perceived as less interested in research-a perception that seems likely to influence study personnel's recruitment decisions.…”
Section: Lesson 1: Success In Engaging Women Requires Funding and Institutional Supportmentioning
confidence: 99%
“…[46][47][48][49] Attention to structural level drivers of health inequity is a key element of patient-centered-care 50,51 and a critical component of meaningful community engagement. 52,53 Anecdotal evidence suggests that study personnel are sometimes reluctant to enroll women whom they perceive as potentially unable to complete the study and likely to leave the study prematurely which would reflect poorly on the enrolling clinical site. A 2007 survey of ACTG study coordinators and nurses found that women, people color, and people with a history of injection drug use were perceived as less interested in research-a perception that seems likely to influence study personnel's recruitment decisions.…”
Section: Lesson 1: Success In Engaging Women Requires Funding and Institutional Supportmentioning
confidence: 99%